2021
DOI: 10.3390/polym13040509
|View full text |Cite
|
Sign up to set email alerts
|

Study Analysis of Thermal, Dielectric, and Functional Characteristics of an Ethylene Polyethylene Diene Monomer Blended with End-of-Life Tire Microparticles Amounts

Abstract: The recycling and disposal of disused tires is a topic of great concern to today’s companies, researchers, and society in general. In this sense, our research aims to recycle end-of-life tires (GTRs) through the separation of the fraction of vulcanized rubber from the other compounds in order to later grind this fraction and separate it into lower particle sizes. Finally, we aim to incorporate these GTR particles as a filler of an ethylene-polyethylene-diene monomer (EPDM). The obtained composites with EPDM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…The values of dielectric constant for EPDM/flax composites increase gradually with the flax loading. A similar conclusion was reported by Marin-Genesca and coworkers for ethylene propylene diene monomer blended with grinding recycled tire microparticles [ 28 ]. We believe that the reactive polar groups of the flax fibers cause an intense dipolar activity and consequently boost the dielectric constant of EPDM/flax composites.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The values of dielectric constant for EPDM/flax composites increase gradually with the flax loading. A similar conclusion was reported by Marin-Genesca and coworkers for ethylene propylene diene monomer blended with grinding recycled tire microparticles [ 28 ]. We believe that the reactive polar groups of the flax fibers cause an intense dipolar activity and consequently boost the dielectric constant of EPDM/flax composites.…”
Section: Resultssupporting
confidence: 88%
“…The E0 sample exhibits the lowest magnitude of ε′ due to the low polarity of the neat polymer backbone [ 29 ]. Besides, the low value of dielectric constant for neat EPDM was observed by other authors [ 28 , 29 ]. The values of dielectric constant for EPDM/flax composites increase gradually with the flax loading.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…All EPDM blends shared its characteristic peaks, evident by the presence of the glass transition temperature ( T g ) at ≈−50 °C, followed by a broad feature that ended with another endothermic peak at (≈40 °C), the latter is attributed to melting of crystallites grown during storage. [ 35 ] The occurrence/disappearance of this peak is thought to be related to the phase mixing quality within the samples. At higher temperatures, blends exhibited a reversible peak at 165 °C, correlating to the T m of PP.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research works explore waste composite polymeric materials as potential materials for use in electrical insulation [ 5 , 6 , 7 , 8 , 9 ], generally for low insulation requirements. The present research is shown the structural-dielectric behavior from mixtures using one of the most used polymers in the industry such as polyethylene, in its most common varieties: high density (HDPE) and low density (LDPE).…”
Section: Introductionmentioning
confidence: 99%